High-speed packet access evolution in 3GPP release 7. - Holma, Harri (IEEE Communications magazine)
High-speed packet access (HSPA) was included in third generation partnership project (3GPP) releases 5 and 6 for downlink and for uplink. The 3GPP release 7 offers a number of HSPA enhancements, providing major improvements to the end-user performance and to network efficiency. The release 7 features are introduced in this paper. Release 7 also is known as HSPA evolution or HSPA+. The HSPA+ downlink peak bit rate can be increased to 28.8 Mbps with a multiple input multiple output (MIMO) antenna solution, and the uplink rate can be increased to 11.5 Mbps with higher order modulation in release 7. The higher peak rates are facilitated by the layer 2 optimization in downlink. In addition, the terminal power consumption can be reduced considerably for packet applications. The downlink cell capacity will be enhanced with new types of terminal requirements for a two-antenna equalizer and with MIMO. Altogether, release 7 features nearly double the cell capacity compared to release 6 with emphasis on the capacity of voice-over-IP (VoIP) service. 3GPP release 7 enables the simplification of the network architecture. The number of network elements for the user plane can be reduced from four in release 6 to two in release 7. The HSPA flat architecture in release 7 is similar to the architecture agreed upon for 3GPP long-term evolution (LTE), thus enabling the later, smooth evolution from HSPA to LTE. LTE will be specified as part of release 8 and further push the radio capabilities higher with larger bandwidth and lower latency. The LTE performance target is to provide two-to-four times the performance of the HSPA release 6 reference case [1]. 3GPP release 7 and 8 solutions for the HSPA evolution will be worked in parallel together with the LTE development, and some aspects of the LTE work are expected to reflect on the HSPA evolution as well. 3GPP release 7 was completed in June 2007, with some work remaining on the performance requirements. Commercial deployment and devices - are expected by 2009.